On the revision of detecting learning-by-exporting: empirical evidence from small- and medium-sized enterprises in Vietnam - Nguyen, Ngoc; Nguyen, Huong; Dao, Tien (Journal of International Economics and Management, 2023)
This study aims to identify the role of exports in improving the productivity of small- and medium-sized enterprises (SMEs) in Vietnam. By applying the propensity score matching method, we exploit the firm-level panel dataset from the Vietnam SME Survey between 2009 and 2014. This remarkable period occurred two years after Vietnam’s accession to the World Trade Organization. Hence, for the first time, the learning-by-exporting hypothesis was tested for a case study of SMEs in developing countries in the context of international trade integration, such as Vietnam. This paper shows that SMEs in Vietnam could improve their productivity when exporting during the studied period. We also find that exports have a significant impact on the productivity of SMEs in non-municipal areas of Vietnam. Based on these findings, policy recommendations are withdrawn for stimulating the productivity of SMEs in developing countries. In particular, SMEs in non-municipal provinces might need more favorable policies to boost export activities.